Rodent models of Parkinson's disease: beyond the motor symptomatology - Campos, Filipa L.; Carvalho, Miguel M.; Cristovão, Ana C.; Je, Goun; Baltazar, Graça; Salgado, António J.; Kim, Yoon-Seong; Sousa, Nuno (Frontiers in Behavioral Neuroscience, 2013)
Parkinson's disease (PD) is classically characterized by motor symptoms; however, non-motor symptoms (NMS) are increasingly recognized as relevant in disease-state, given the associated alterations in mood (depression and anxiety) and cognition. Here, particularly in regards to NMS, we aimed to compare the motor, emotional and cognitive behavior of three animal models of PD that trigger dopaminergic (DAergic) degeneration on both brain hemispheres: (i) the 6-hydroxydopamine (6-OHDA, 8 or 6 μg) lesion model; (ii) the paraquat (PQ) induced model, and (iii) a genetic model based on α-synuclein overexpression (α-syn). 6-OHDA and α-syn vector were injected bilaterally in the substantia nigra pars compacta (SNpc) of adult male Wistar rats; as for PQ delivery, micro-osmotic pumps were implanted in the interscapular region. Motor deficits were observed in all models, with histological analysis of tyrosine hydroxylase positive cells in the SNpc revealing a significant loss of DAergic neurons in all animal models. In addition, the α-syn animal model also presented a reduction in exploratory activity, and the 6-OHDA and PQ animals displayed a significant increase in both depressive- and anxiety-like behavior. Interestingly, cognitive impairment (working memory) was only observed in the 6-OHDA model. Overall, these PD models are suitable for mimicking the motor symptoms associated to PD, with each encompassing other relevant NMS components of the disorder that may prove beneficial for further studies in PD.